(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This essay examines the role of the Italian delegation in the negotiations that led to the establishment of the Review Mechanism of the Palermo Convention and offers some thoughts about the subsequent strengthening of international cooperation